2017
DOI: 10.21474/ijar01/3013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Rhino Sinusitis and It's Recurrent After Treatment Compare to Its Recurrent After Surgery at Saudi Arabia, 2016.

Abstract: Objectives:To assess the prevalence of Chronic Rhinosinusitis in Saudi Arabia, identify the most affected age group and Gender, assess the most common risk factors for Rhinosinusitis and determine recurrent of Rhinosinsitis after treatment and after surgery and to compare them. Methods: A cross-sectional study which was conducted electronically through a random sampling includes434 person from Saudi Arabia during 2016. The used questionnaire includes 20 questions and was formulated to include demographic aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
4
17
2
Order By: Relevance
“…A study from China [10] showed that chronic sinusitis was more prevalent in males. In the contrary to the previous findings, it was found in a Saudi study [7] that the majority of participants who had chronic sinusitis were females (61.6%).…”
Section: Table2: Correlation With Demographics and Sinusitiscontrasting
confidence: 83%
See 4 more Smart Citations
“…A study from China [10] showed that chronic sinusitis was more prevalent in males. In the contrary to the previous findings, it was found in a Saudi study [7] that the majority of participants who had chronic sinusitis were females (61.6%).…”
Section: Table2: Correlation With Demographics and Sinusitiscontrasting
confidence: 83%
“…Also, the large majority had no aspirin sensitivity (98.5%), no immune system disturbance (95.5%) and 91.9% weren't exposed to pollution, there were 37.3% had an allergy. The prevalence of chronic sinusitis in this study was 25.3%, while the prevalence in Korean population was reported as 1.01% [21] , in the USA it represented 12% [13] and in Europe, it was 10.9 % of the population [9] .In a previous Saudi study [7] half of the participants included in the study had chronic sinusitis.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations